Synthesis of novel magnetic carbon nano-composite from waste biomass: A comparative study of industrially adoptable hydro/solvothermal co-precipitation route. Issue 2 (April 2020) - Siddiqui, M.T.H; Ahmed Baloch, Humair; Nizamuddin, Sabzoi; Haris, Muhammad; Mubarak, N.M; czajka, Michael; Khalid, Mohammad; Griffin, G.J; Srinivasan, Madapusi
Abstract: Development of advanced magnetic carbon nano-materials has provided new dimensions in numerous research areas due to their multiple applications. In this study, novel magnetic carbon nano-composites were synthesised by integration of magnetic nanoparticle on novel graphene and renewable carbon materials from rice husk. Magnetic carbon nano-composites were fabricated by hydrothermal carbonization-coprecipitation (HTCC) and solvothermal carbonization-coprecipitation (STCC) routes that are easily scalable. The objective of this work is a comparative study of HTCC and STCC processed and their products. The experiments were conducted using different process variables including process temperatures (180, 220 and 260 °C), process time (0.5, 1 and 2 h) and solvents (water and ethanol). Chemical interaction of well-dispersed magnetic nano-particles of 5–20 nm size with carbonaceous material was confirmed. Magnetically recoverable nano-composite is highly suitable for use in multiple applications including catalysis, super-capacitance, biosensing devices, environmental remediation and enzymes immobilization and can establish various opportunities for industry in future.